Implementasi Sanksi Denda (Nadzar) Dalam Transaksi Pembiayaan Murabahah - Bernad Hananto; Wiranta; Suhrowardi; Iin Masriah; Rahadian SA (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2024)
The purpose of this study is to describe the implementation of the Murabahah (buying and selling) house contract, to describe the implementation of fines / Nadzar if the customer / member is late in paying, and to find out the concept of applying the fine sanctions in a sharia perspective. This research uses a qualitative research approach, while this type of research is descriptive in nature, which describes an event. By using primary data through interviews and social media as well as secondary data taken through literature review.The results of this study are the fines imposed at BMT UGT Sidogiri Cikarang amounting to 0.17% per day of the principal amount of financing arrears. And the fines are in accordance with the DSN fatwa No. 17 / DSN-MUI / IX / 2000, where if there is a customer / member who is able to pay but delays payment, he will be subject to fines / ta'zir , which will be imposed as social funds. However, there are some scholars who do not allow the fine, because it is tantamount to usury.